In-situ springback compensation in incremental sheet forming. Issue 1 (2019) - Ren, Huaqing; Xie, Jiaxi; Liao, Shuheng; Leem, Dohyun; Ehmann, Kornel; Cao, Jian
Abstract: Limited geometric accuracy in incremental sheet forming is a major obstacle for its wide adoption in industry. This paper develops a generic methodology, suitable for arbitrary part geometries and various ISF processes, for addressing one of the main causes of geometric inaccuracy, i.e., in-process springback. The methodology consists of three main elements: determination of key control points to treat geometric complexity, simplified simulation models to predict springback offline, and in-situ toolpath modification during forming. It is shown experimentally that the method provides an efficient and robust solution for various geometries with negligible setup cost.